COMPARISON BETWEEN MECHANICAL PROPERTIES AND MICROSTRUCTURE OF ALLOY TI-6AL4V, COLD WORK VERSUS PROTOTIPES BY DIRECT METAL LASER SINTERING - Gregolin, R. F. [UNESP]; Lenquist, T. M. [UNESP]; Anibal, M. C. [UNESP]; Borghi, D. S. [UNESP]; Tokimatsu, R. C. [UNESP] (Inegi-inst Engenharia Mecanica E Gestao Industrial, 2012)
The present work aims to study the microstructure and mechanical properties of titanium alloys, widely used in the manufacture of orthopedic implants in order to compare a new manufacturing technology of implants, rapid prototyping in metals with conventional manufacturing processes. Rapid prototyping is being used in many areas of human knowledge to assist in the study and often in the manufacture of components for their own use. Nowadays with the advancement of software and equipment such as computed tomography and magnetic resonance imaging, we can reproduce any part of the human body in three-dimensional images with great perfection and it is used in the reproduction of implants, scaffolds, material aid and preparation in surgery. This work aims to do: A comparison between the microstructure of the alloy in the two manufacturing processes (prototyping and conventional), showing the grain size, the nature, form, quantity, and distribution of various ingredients or certain inclusions and study of mechanical properties of titanium in both cases.